EFEKTIVITAS PENGGUNAAN DOMPET DIGITAL (E-WALLET) SEBAGAI ALAT TRANSAKSI PERSPEKTIF ‘URF - Laili Rifda Mahdia Abidin (Irtifaq : Jurnal Ilmu-Ilmu Syari’ah, 2025)
Digital wallets or E-wallets play a very important role in changing society. A digital wallet (e-wallet) is an electronic service for storing payment instrument data using electronic money that can hold funds. E-wallet is considered an effective transaction tool because it is easy to use, efficient and practical, the use of e-wallets is a new habit ('urf) for the general public in carrying out digital-based transaction activities, the author wants to know how the 'urf perspective on the practice of using Digital Wallets (e-wallets) as a transaction tool for lecturers at the Faculty of Islamic Religion, Hasyim Asy'ari Tebuireng University Jombang.The author uses qualitative research with a phenomenological approach. Data collection techniques are carried out by interview, observation, and documentation. The results of the interviews obtained state that the use of e-wallets as a transaction tool is very easy with features that suit the needs and use of e-wallets and in the view of ‘urf, this e-wallet is classified as ‘urf shahih, because the purpose of use is carried out as needed and not excessive. so that it is effective in helping to facilitate transactions in the midst of busy activities and still paying attention to the provisions of Islamic law.